Buku Jihad Terjemahan dari Bahasa Arab dan Potensi Radikalisme Beragama di Lembaga Pendidikan - Abdul Munip (IAIN Ponorogo, 2017)
This paper describes how the jihad books translated from Arabic potentially strengthen radicalism in Indonesia. In fact, the jihad books are written and translated by the jihadists themselves as their reference for acting global jihad. These books are disseminated by their publisher or posted in their website. Most of these jihadists website provide information, articles and eBooks that can be downloaded for free. Most of these books discuss about the meaning, law, financing, strategy and targets of jihad. There are a number of concepts that potentially affect the readers toward an attitude of radicalism. These concepts are jihad is war, suicide bombing is part of jihad, and the thoghut government is a target of their jihad. These translated books also potentially affect the growth of a radical and intolerant attitude in educational institutions, because it can creep through the mentoring activities of the Islamic religion in College, Rohani Islam (Rohis) in SMA/SMK, friendship networks and hidden agendas of the institution's manager who opposed the ideology of the State. Therefore, to minimize the negative impact of the these translated books, the concept of soft jihad is need to be introduced and promoted.تبين هذه المقالة عن إحتمال كتب الجهاد المترجمة من العربية فى تعزيز التطرف الدينى في إندونيسيا. وفي الواقع، أنّ الكاتبين والمترجمين لهذه الكتب هم الجهاديون أنفسهم ليجعلونها مصادر فى عمليتهم الجهادية العالمية. وتنشرهذه الكتب مطبعة او منشورة فى مواقعهم على الإنترنت. وتوفر معظم هذه المواقع المعلومات والمقالات والكتب الإلكترونية التي يمكن تحميلها مجاناً. وكثير من هذه الكتب يتحدث حول معنى الجهاد، وحكمه، وتمويله، واستراتيجيته، ومن يجب عليهم القتل. وهنا كعدد منا لمفاهيم الجهادية التي يحتمل أن تؤثرعلى القرّاء إلى التطرف الديني. ومن هذه المفاهيم أن الجهاد هو الحرب او القتل لا غير، وأن التفجيرالانتحاري هوجزء من الجهاد ويسمونه بعملية إستشهادية، وان الحكومة الطاغوتية هي التى يجب عليها الحرب أو القتل. وتحتمل هذه الكتب المترجمة الجهادية أن تؤثر على نمو المواقف المتطرفة والمتعصبة في المؤسسات التعليمية، وذلك من خلال أنشطة الإرشاد إلى الدين الإسلامي (mentoring Agama Islam) في اكثر الجامعات، ومن خلال أنشطة المنظمة الطلابية الإسلامية (Rohis) في SMA/SMK، ومن خلال الصداقة الشبكة بين الطلاب، وكذلك من خلال البرامج الخفية لدى المؤسسات التعليمية التى تعارض أيديولوجية الحكومة الإندونسية. ولذلك، ينبغى أن يقدم مفهوم الجهاد اللينة لدى المسلمين الإندونسيين لنقصان الأثرالسلبي لهذه الكتب المترجمة.